Determinants of access to and use of gestational diabetes mellitus services in Kenya: a multimethod case study protocol - Jacob Spallek; Marie Tallarek; Angela Obongo (BMJ Open)
Introduction Gestational diabetes mellitus (GDM) is a growing public health issue in many low and middle-income countries (LMICs), making up about 90% of the global burden of GDM. Additionally, LMICs’ healthcare systems are already overwhelmed by the prevalence of communicable diseases. It is crucial to understand the patterns of GDM in sub-Saharan African countries. Early detection, lifestyle and medication interventions, regular prenatal visits and effective postpartum management can help avert the future development of type 2 diabetes. GDM services present opportunities for preventive and treatment strategies for women with GDM. However, various factors contribute to challenges and obstacles in accessing GDM services, particularly suboptimal postpartum screening and follow-up. This study aims to investigate the societal and healthcare factors that facilitate or hinder access to and use of GDM services, as well as the factors that promote or obstruct the management and treatment of GDM, in Kenya, using a postcolonial theoretical approach.Methods and analysis The proposed study design is a multimethod case study of Kenyan GDM services. Data analysis is descriptive and thematic using SPSS software and qualitative content analysis. Data will be drawn from document reviews from the National Health Services (NHS), conversations with experts, on-site observations, semistructured questionnaires and face-to-face interviews. The study subjects are purposively sampled healthcare providers (n=15) working in clinics and hospitals offering diabetes services, purposively sampled women who have been diagnosed with GDM identified from health records (n=15) and NHS experts (n=2). The study will take place in maternal healthcare services sites in national referral hospitals and/or private hospitals (two urban and two semiurban hospitals) in Nairobi and Kisumu, Kenya.Ethics and dissemination The study has obtained ethical approval from the ethical committees of three institutions: Brandenburg University of Technology Cottbus-Senftenberg (EK2021-03) in Germany and Jaramogi Oginga Odinga Teaching and Referral Hospital (ISERC/1B/VOL.II/558/21) and Maseno University (MSU/DRPI/MUERC/00969/21) in Kenya. A research permit has been granted by the National Commission for Science, Technology and Innovation in Kenya. Participation in the study requires a signed informed consent form. The study findings will be shared with the scientific community and the study sites through scientific journals, academic presentations and public health and diabetes-related posters.